2016
DOI: 10.1038/nm.4213
|View full text |Cite
|
Sign up to set email alerts
|

PIM1 kinase inhibition as a targeted therapy against triple-negative breast tumors with elevated MYC expression

Abstract: Triple-negative breast cancer (TNBC), which lacks the expression of the estrogen, progesterone, and HER2 receptors, represents the breast cancer subtype with the poorest outcome1. No targeted therapy is available against this subtype due to lack of validated molecular targets. We previously reported that MYC signaling is disproportionally elevated in triple-negative (TN) tumors compared to receptor-positive (RP) tumors2. MYC is an essential, pleiotropic transcription factor that regulates the expression of hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
142
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(155 citation statements)
references
References 67 publications
8
142
0
Order By: Relevance
“…We found that PIM1 knockdown upregulated CDKN1B/ p27, suggesting a mechanism by which PIM1 promotes cell cycle progression in TNBC. Our findings concord with the findings from Horiuchi et al 43 (personal communication) and indeed, others have shown that PIM1 downregulates p27 at transcriptional and post-transcriptional levels 37 in other contexts. We show for the first time that PIM1 knockdown decreased the expression of PTPN11 and EPHA2, genes of significant relevance in breast cancer 15,16 : PTPN11, encodes phosphatase SHP2, involved in breast cancer progression and maintainance of tumor-initiating cells 15 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that PIM1 knockdown upregulated CDKN1B/ p27, suggesting a mechanism by which PIM1 promotes cell cycle progression in TNBC. Our findings concord with the findings from Horiuchi et al 43 (personal communication) and indeed, others have shown that PIM1 downregulates p27 at transcriptional and post-transcriptional levels 37 in other contexts. We show for the first time that PIM1 knockdown decreased the expression of PTPN11 and EPHA2, genes of significant relevance in breast cancer 15,16 : PTPN11, encodes phosphatase SHP2, involved in breast cancer progression and maintainance of tumor-initiating cells 15 .…”
Section: Discussionsupporting
confidence: 92%
“…PIM1 knockdown downregulated transcription of a subset of MYC-target genes including MCL1 through mechanisms such as phosphorylation of Histone-H3 at Ser10 and phosphorylation of c-MYC at Ser62, known to be required for c-MYC-driven transcriptional activation and oncogenic transformation 10,30 . Altogether, our data support PIM1 as a potential target in basal-like TNBCs, including the MYC-driven group, and are supported by the independent study by Horiuchi et al 43 (personal communication), which demonstrates that c-MYC overexpression generates PIM1 essentiality in mammary epithelial cells and further proposes that PIM1 function is needed to support c-MYC-dependent malignancy in TNBC cells 43 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, PIM2 overexpression in mice could promote breast cancer tumorigenesis (Jimenez‐Garcia et al ., ). But the mechanisms of PIM2 by which regulates breast cancer cell proliferation are still unclear, Our data showed that PIM2 was crucial in the regulation of TTP‐reduced proliferation and migration in breast cancer cells, consistent with previous studies (Horiuchi et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…phosphorylating the inhibitory site Ser83 on ASK1 (25), and PIM1 has been correlated with tumor aggressiveness and poor survival in TNBC (62). Combining NOS inhibition therapy with docetaxel may prevent activation of PIM1, resulting in a decrease of pASK1 Ser83 levels and an increase in pASK1 Thr845 levels, which result in activation of effector proteins JNK and cleaved caspases 3 and 9 (Fig.…”
Section: Discussionmentioning
confidence: 98%